SEX DETERMINATION USING CRANIOMETRIC MEASUREMENTS OF MASTOID PROCESS: SEX DETERMINATION USING CRANIOMETRIC MEASUREMENTS OF MASTOID PROCESS - K. T, Sivaranjani.; Sumathy, Govindarajan; M S, Premkumar; Vinesh, E.; E. Rajesh, E. Rajesh (Journal of Neonatal Surgery, 2025)
This study is to evaluate the accuracy of different craniometric parameters of mastoid process in sex determination. Sex determination is one of the most important parameters in anatomy and forensic science. In the skull, the mastoid process is a compact permanent process and is more resistant to damage. Hence, it can be used as a marker of sex determination in unidentified human skull remains. The study was conducted on 50 adult dry human skulls of unknown age from the Department of Anatomy at Sree Balaji Dental College and Hospital, Chennai. The craniometrical points like highest part of external auditory meatus (porion), lowest point of mastoid process (mastoidale), Asterion (the meeting point of three sutures i.e. lambdoid, occipitomastoid and parietomastoid) were selected as area of our study. A triangle was prepared/drawn using these three points on skull bone on both sides. The measurements were taken from both sides, i.e., right and left side, and then an average of both sides was considered for statistical analysis. The outcome showed a significant higher values in male than the female dry specimens. The mastoid measurements can serve as an invaluable tool to the forensic scientist with respect to identifying the sex of unknown individuals and as a relevant tool for craniofacial surgeons.